2012
DOI: 10.1037/a0026519
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive patterns of stress responsivity: A preliminary investigation.

Abstract: The adaptive calibration model (ACM) is an evolutionary–developmental theory of individual differences in stress responsivity. In this article, we tested some key predictions of the ACM in a middle childhood sample (N = 256). Measures of autonomic nervous system activity across the sympathetic and parasympathetic branches validated the 4-pattern taxonomy of the ACM via finite mixture modeling. Moreover, the 4 patterns of responsivity showed the predicted associations with family stress levels but no associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 99 publications
11
127
0
2
Order By: Relevance
“…One difference between our work and other studies supporting these models is that previous investigations have focused on younger children. (28) Given the developmental changes in stress reactivity that occur during adolescence, it will be important for future studies to replicate our findings in younger samples.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…One difference between our work and other studies supporting these models is that previous investigations have focused on younger children. (28) Given the developmental changes in stress reactivity that occur during adolescence, it will be important for future studies to replicate our findings in younger samples.…”
Section: Discussionmentioning
confidence: 79%
“…(20, 25, 26) An extension of this theory, the adaptive calibration model, describes a wider variety of stress response system profiles that may emerge depending on the severity and chronicity of early-life adversity. (27, 28) Although existing theories are supported by evidence from studies of children exposed to less extreme forms of adversity, (20, 26, 28) they do not explain the disparate findings with regard to CM specifically. Biological sensitivity to context argues that extreme adverse environments should lead to elevated physiological reactivity,(24) and adaptive calibration posits that, due to evolutionary sex differences in optimal reproductive strategies in environments characterized by extreme threat, elevated physiological reactivity among females and blunted reactivity among males should be observed following traumatic stressors.…”
mentioning
confidence: 93%
“…However, both from a theoretical and empirical viewpoint there is reason to believe that the role ANS reactivity plays in the association between adversity and antisocial behavior is different in boys and girls. Evolutionary theorists have argued that in stressful environments it is more adaptive for females to be vigilant and attentive to environmental cues and thus show heightened ANS reactivity, with more internalizing problems as a result (Del Giudice, Hinnant, Ellis, & El-Sheikh, 2012;Glover & Hill, 2012). In contrast, in males it may be more important to respond less to environmental cues, as they are more programmed towards exploring and competing with other males, which may result in antisocial behaviors (Del Giudice et al, 2011).…”
Section: Perinatal Adversities and Antisocial Behaviormentioning
confidence: 92%
“…Strategies for boys involve more unemotional responsivity patterns, as this is helpful for engaging in risky activity, whereas strategies for girls are likely to involve more vigilant responsivity patterns to cope effectively with threats in the environment. A recent study indeed showed that girls experiencing high levels of environmental stress were more likely to be in the vigilant (i.e., heightened stress responses) class(Del Giudice et al, 2012). Boys who experienced high levels of environmental stress were often in the unemotional (i.e., blunted stress response) class.…”
mentioning
confidence: 96%
“…1,4,34,48 However, it is important to note that investigations of maternal depression and cortisol in pregnancy have reported mixed results. 12,13,[49][50][51][52][53][54] Nonetheless, it has been suggested that biological markers of prenatal stress may be better indicators of offspring outcomes than selfreport measures.…”
Section: Discussionmentioning
confidence: 99%